Comparative Analysis of Anesthetic Techniques in General Surgery, Evaluating Outcomes, Medical Complications, and Recovery Profiles - Hafeezullah, Misbah Arif, Jamshed Bashir, Faisal Toheed, Mobasher Ahmad Saeed, Ghashia Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anesthetic technique has an important role in determining surgical outcomes by affecting intraoperative stability, postoperative recovery, and complication rates. In this study, GA was compared to RA and LA/S in general surgery regarding its effects on hemodynamic stability, pain control, and postoperative morbidity. Methods: A prospective observational study was carried out in 120 adult patients who were subjected to general surgery and were divided into three groups (GA: n = 40; RA: n = 40; LA/S: n = 40). Parameters intraoperatively, including MAP variability and vasoactive medication use were recorded, while postoperatively pain scores, opioid consumption, length of stay, and complication rates were analyzed. Complications were identified as independent predictors of complications by multivariate logistic regression. Results: MAP variability (12.4 ± 3.5 mmHg, p = 0.03), as well as use of vasoactive medications (35% vs. 20% in RA, 15% in LA/S, p = 0.04) was greater in GA. GA patients also had longer PACU (90 ± 25 min, p < 0.001) and hospital stays (4.2 ± 1.1 days, p = 0.002), higher pain scores (VAS 6.2 vs 4.1 and 4.3, p < 0.001), and higher opioid consumption (p < 0.001). GA was confirmed as an independent predictor of complications by multivariate analysis (OR 2.5; p = 0.028). Conclusion: The association with higher hemodynamic instability, longer recovery, and greater complications is greater for GA than RA and LA/S. If feasible, RA and LA/S should be preferred to improve surgical outcomes. Keywords: General anesthesia, regional anesthesia, local anesthesia with sedation, postoperative recovery, hemodynamic stability, surgical outcomes, perioperative complications, opioid consumption, enhanced recovery.